2020
DOI: 10.5267/j.msl.2020.3.028
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived environment restorative qualities on Chinese visitors’ satisfaction in rural destination

Abstract: With rapid economy development and increasing social competition, the majority of Chinese people living in the city is suffering from daily work and life stress. Due to the inflexible holiday system, Chinese city people prefer visiting a rural destination around the place where they live, which is identified as restorative environment, with the demand of rest and mental replenishment. In order to investigate how perceived rural destination environment qualities influence visitor's satisfaction, this empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
2
0
2
Order By: Relevance
“…In the three tourist spaces analysed, when the visitors rate the space as highly restorative, they report higher levels of satisfaction on these three indicators, and as perceived restorative capacity decreases, so does satisfaction. These results support the second hypothesis and align with those found in previous studies (Cho & Lee, 2016;Kim et al, 2014;Lehto, 2013;Lehto et al, 2017;Lu & Amponstira, 2020). These differences were more pronounced in the coastal urban boardwalk, a tourist space that has more urban elements that can lower the impact of the natural elements compared to the other two places, as natural elements tend to possess the restorative qualities of being away, fascination, compatibility and extent to a higher degree (Berto, 2014;Kaplan & Kaplan, 1989).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the three tourist spaces analysed, when the visitors rate the space as highly restorative, they report higher levels of satisfaction on these three indicators, and as perceived restorative capacity decreases, so does satisfaction. These results support the second hypothesis and align with those found in previous studies (Cho & Lee, 2016;Kim et al, 2014;Lehto, 2013;Lehto et al, 2017;Lu & Amponstira, 2020). These differences were more pronounced in the coastal urban boardwalk, a tourist space that has more urban elements that can lower the impact of the natural elements compared to the other two places, as natural elements tend to possess the restorative qualities of being away, fascination, compatibility and extent to a higher degree (Berto, 2014;Kaplan & Kaplan, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…En los tres espacios turísticos analizados, cuando los visitantes valoran el espacio como muy restaurador reportan mayores niveles de satisfacción en sus tres indicadores, y a medida que decrece la capacidad restauradora percibida disminuye la satisfacción. Estos resultados apoyan la segunda hipótesis y van en la línea de los obtenidos en investigaciones previas (Cho & Lee, 2016;Kim et al, 2014;Lehto, 2013;Lehto et al, 2017;Lu & Amponstira, 2020). Estas diferencias fueron más acusadas en el paseo urbano costero, un espacio turístico que, frente a los otros dos lugares analizados, presenta más elementos urbanos que pueden reducir el impacto de los elementos naturales, que suelen poseer en mayor medida las cualidades restauradoras de evasión, fascinación, compatibilidad y extensión (Berto, 2014;Kaplan & Kaplan, 1989).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Fascination and compatibility can predict satisfaction and behavioral intention after visiting forest resorts. According to a survey of Chinese visitors visiting Thailand, Lu and Ampostira [68] found that mental getaways, compatibility, and fascination assessed based on the PDRQs scale have a significant effect on satisfaction. Based on the abovementioned research, this study proposed the following hypothesis: H3 .…”
Section: Perceived Restorativeness and Satisfactionmentioning
confidence: 99%